Why privacy matters - Richards, Neil (Professor of law) (New York, NY Oxford University Press, 2022)
any people tell us that privacy is dead, or that it is dying, but such talk is a dangerous fallacy. This book explains what privacy is, what privacy isn't, and why privacy matters. Privacy is the extent to which human information is known or used, and it is fundamentally about the social power that human information provides over other people. The best way to ensure that power is checked and channeled in ways that benefit humans and their society is through rules - rules about human information. And because human information rules of some sort are inevitable, we should craft our privacy rules to promote human values. The book suggests three such values that our human information rules should promote: identity, freedom, and protection. Identity allows us to be thinking, self-defining humans; freedom lets us be citizens; while protection safeguards our roles as situated consumers and workers, allowing us, as members of society, to trust and rely on other people so that we can live our lives and hopefully build a better future together.
his is a book about what privacy is and why it matters. Governments and companies keep telling us that Privacy is Dead, but they are wrong. Privacy is about more than just whether our information is collected. It's about human and social power in our digital society. And in that society, that's pretty much everything we do, from GPS mapping to texting to voting to treating disease. We need to realize that privacy is up for grabs, and we need to craft rules to protect our hard-won, but fragile human values like identity, freedom, consumer protection, and trust.
Introduction: The Privacy Conversation -- Part I: How to think about privacy -- What Privacy Is -- A Theory of Privacy as Rules -- What Privacy Isn't -- Part II:Three privacy values -- Identity -- Freedom -- Protection -- Conclusion: Why Privacy Matters.
Includes bibliographical references and index.
Chicago-Kent College of Law / Roy C. Palmer Civil Liberties Prize, 2022
Keywords: Civil rights. -- Electronic book; Consumer protection; Identité (Psychologie); Identity (Psychology); Privacy, Right of; Data protection -- Law and legislation; Privacy, Right of -- Social aspects; Protection de la vie privée; Protection of privacy; Consummators -- Protection; Data protection legislation; Data protection; LAW -- General; Privacy, Right of -- In; Identity (Psychology) -- Protection; Consumer protection -- Da; Protection des données à caractère personnel. -- Civil rights; Civil rights -- Consumer protection; Consumer protection -- Law and legislation -- Identity; Consumer Advocacy